2005
DOI: 10.5551/jat.12.154
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Aggregation and Vasoconstriction Related to Platelet Cyclooxygenase and 12-Lipoxygenase Pathways

Abstract: Many thrombotic angiopathies originate as a result of an abnormal interaction between platelets and blood vessel walls. The present study focused on the platelet activating factor (PAF)-induced platelet aggregation mechanism and was undertaken to clarify the association between platelet aggregation and vasocontractility. Vasoconstriction was examined in perfused artery segments dissected from the central ear artery of male rabbits. Autologous platelet rich plasma (PRP) was infused into the perfusion system. Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…PDMPs reportedly play a pivotal role in the acute occlusion of atherosclerotic small arteries or arterioles where pathological levels of fluid shear stress can be found 1,[40][41][42] . Clinically, elevated levels of plasma PDMP are associated with thrombotic disorders 12,18,27,30) .…”
Section: Discussionmentioning
confidence: 99%
“…PDMPs reportedly play a pivotal role in the acute occlusion of atherosclerotic small arteries or arterioles where pathological levels of fluid shear stress can be found 1,[40][41][42] . Clinically, elevated levels of plasma PDMP are associated with thrombotic disorders 12,18,27,30) .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, conflicting data have been observed with regard to the association of platelet biomarkers with prognosis. 7,9,21,23,24 Notably, the small size of these previous studies underscores the need for ongoing exploration of the biology of platelet activation in HF. n/a n/a n/a n/a Kandis et al 10 Acute vs chronic HF Acute>chronic HF Yes n/a n/a n/a n/a n/a n/a n/a No differences between groups; decrease at followup for acute HF n/a n/a n/a n/a …”
Section: Evidence Of Platelet Activation In Hfmentioning
confidence: 99%
“…In fact, the platelet response to agonists, such as ADP, involves not only platelet aggregation but also secretion of several vasoactive agents, such as serotonin and thromboxane A2. 7 Animal models have demonstrated that these substances cause vasoconstriction and further promote platelet aggregation.…”
Section: Pathophysiology Of Platelet Activationmentioning
confidence: 99%
See 2 more Smart Citations